Development and Evaluation of a Cognitive Aid Booklet for Use in Rapid Response Scenarios. Issue 4 (August 2019) - Mitchell, Oscar J. L.; Lehr, Andrew; Lo, Michelle; Kam, Lily M.; Andriotis, Anthony; Felner, Kevin; Kaufman, Brian; Madeira, Charles
Abstract : Introduction: Rapid response teams (RRTs) have become ubiquitous among hospitals in North America, despite lack of robust evidence supporting their effectiveness. Many RRTs do not yet use cognitive aids during these high-stakes, low-frequency scenarios, and there are no standardized cognitive aids that are widely available for RRTs on medicine patients. We sought to design an emergency manual to improve resident performance in common RRT calls. Methods: Residents from the New York University School of Medicine Internal Medicine Residency Program were asked to volunteer for the study. The intervention group was provided with a 2-minute scripted informational session on cognitive aids as well as access to a cognitive aid booklet, which they were allowed to use during the simulation. Results: Resident performance was recorded and scored by a physician who was blinded to the purpose of the study using a predefined scoring card. Residents in the intervention group performed significantly better in the simulated RRT, by overall score (mean score = 7.33/10 and 6.26/10, respectively, P = 0.02), and by performance on the two critical interventions, giving the correct dose of naloxone (89% and 39%, respectively, P < 0.001) and checking the patient's blood glucose level (93% and 52%, respectively, P = 0.001). Conclusions: In a simulated scenario of opiate overdose, internal medicine residents who used a cognitive aid performed better on critical tasks than those residents who did not have a cognitive aid. The use of an appropriately designed cognitive aid with sufficient education could improve performance in critical scenarios.